Medicine, media and the law: The effect on training in obstetrics and gynaecology. (February 2021) - McCarthy, C.M.; O'Sullivan, S.; Corcoran, P.; Eogan, M.; Bennett, D.; Horgan, M.; O'Donoghue, K.
Abstract: The inextricable link between medicine and the legal profession has flourished in the 21st century, with countless newspaper articles and social media content on medical cases visible at every juncture. This is particularly true in the speciality of obstetrics and gynaecology, with one of the highest rates of litigation of all medical specialities. We aimed to evaluate the influence of media and the legal environment on the career of trainees in obstetrics and gynaecology. Under the auspices of the Irish national training body, we distributed a 26-item questionnaire to doctors-in-training (DIT) working in obstetrics and gynaecology in the Republic of Ireland. Descriptive statistics and Chi-squared analyses were performed on the anonymised data. 151 DIT responded to the questionnaire, with a response rate of 86.2 % (sample size = 175). The majority were female (79.9 %, n = 121), Irish (85.5 %, n = 106) and had no children (67.0 %, n = 83). 86.7 % (n = 131) felt that the media did not have a positive impact on patients receiving care, and, further, unfairly represented the speciality (94.1 %; n = 142). Additionally, DIT felt that medico-legal issues had a negative impact on issues such as retention and recruitment. These two areas were implicated in over three quarters of DIT considering leaving the speciality. This study demonstrates that DIT perceive media scrutiny and litigation to have a negative effect on the speciality of obstetrics and gynaecology. Further support integrated into specialist training, is needed to ensure that trainees are adequately equipped to deal with both mainstream and social media as well as interactions they may have with the legal profession as they progress through their career.